FAKTOR YANG BERPENGARUH TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI EMPIRIS PADA PT. TELKOMSEL JAWA TENGAH) - Nurul Karim Yustining Tiyas, 12.05.62.0007; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to analyze empirically the effect of the effectiveness of internal control, compliance compensation, observance of the rules of accounting, management information asymmetry and morality against the tendency of the accounting fraud at the Cellular Telecommunications PT (Telkomsel) Central Java region in 2015. The population in this study were employees of the financial Cellular Telecommunication (Telkomsel) Central Java region. In this study, the finance department employees who respond to 50 people. Analysis of the data used is multiple linear regression analysis. The results showed that the effectiveness of internal control, compliance compensation, observance of rules of accounting, management morality significant negative effect on the trend of accounting fraud. While the information asymmetry positive and significant impact on the trend of accounting fraud.Keywords: Effectiveness of Internal Control, Compliance Compensation, Observance of The Rules of Accounting, Information Asymmetry, Moral Management, and Accounting Fraud Trend